IMPLEMENTASI METODE TILAWATI DALAM PEMBELAJARAN AL QUR’AN PADA ANAK-ANAK DI TPA AL FALAH UNIT 081 KOTA BANJARBARU - Muhammad Amin; Muhamad Ramli (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2019)
This study discusses how to implement the method of Tilawati in the study of the Qur'an in TPA Al Falah Unit 081 of Banjarbaru City. The purpose of this research is to determine the implementation of the method of Tilawati on the learning of the Qur'an in children and what are the factors that influence it. The subject in this study is Ustadz, Ustadzah, students and the guardian of the students, while the research object is the implementation of the method of Tilawati in learning to read the Qur'an in children at TPA al Falah Unit 081 City Banjarbaru. In data mining, researchers use observation techniques, interviews, and documentation. Data processing techniques are done by editing, data classification, and data interpretation. Based on the research that the implementation of the method of Tilawati in the study of the Qur'an in children in TPA Al Falah Unit 081 City of Banjarbaru, in general, has been doing very well, this is based on good and the truth of understanding Ustadz and Ustadzah in the implication of the method of Tilawati. While the factors that influence it is the spirit of students and students in learning the Koran, facilities, and infrastructures that support and conducive environment in the study of the Qur'an using the method of Tilawati. Keywords: implementation, Tilawati method, Qur'an learning.